IONESCU-IONESCO, VOIX D’UN EXILÉ ? PROPOSITION D’UNE RELECTURE THÉORIQUE - COȚOFANĂ, Iulian-Emil (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Ionescu-Ionesco, Voice of an Exile? Proposal for a Theoretical Rereading. In this paper, we propose a different reading of Eugène Ionesco’s exile by drawing from a selection of texts from the 1930s and afterwards. As our purpose is to challenge the prevailing discourse surrounding the topic, we have opted to focus on critical and theoretical elements rather than biographical details. We keep in mind that the author’s contributions and the research on his work are two intertwined discourses. In post-1989 Romania, Ionesco is widely regarded as one of the leading literary figures of the Romanian exile. It is our opinion that his exiled status has not been sufficiently investigated, and our aim is to demonstrate that prudence and close reading could uncover some striking nuances that could lead scholars to the solution of a central question: Should Ionescu-Ionesco be regarded as an exile or rather as an expatriate? Ionescu-Ionesco, vocea unui exilat? Propunere pentru o relectură teoretică. În articolul de față propunem o lectură diferită a exilului lui Eugène Ionesco bazându-ne pe o selecție de texte din anii 1930 și de mai târziu. Întrucât scopul nostru este să chestionăm discursul predominant legat de subiect, am ales să ne concentrăm mai curând asupra elementelor critice și teoretice decât asupra detaliilor biografice. Ținem cont de faptul că contribuțiile autorului și cercetarea relativă la opera sa sunt două discursuri întrețesute. În România de după 1989, Ionesco este îndeobște considerat drept o figură literară marcantă a exilului românesc. Opinia noastră este aceea că statutul său de exilat nu a fost suficient investigat, iar obiectivul nostru este să demonstrăm că prudența și lectura atentă pot dezvălui nuanțe remarcabile: ar trebui Ionescu-Ionesco să fie tratat drept un exilat sau mai degrabă drept un expatriat? Cuvinte-cheie: Eugen Ionescu – Eugène Ionesco, exil, expatriat, ideologie, receptare Article history: Received 21 January 2024; Revised 26 March 2024; Accepted 04 June 2024; Available online 25 June 2024; Available print 30 June 2024